Prolonged, brain-wide expression of nuclear-localized GCaMP3 for functional circuit mapping - Kim, Christina K.; Miri, Andrew; Leung, Louis C.; Berndt, Andre; Mourrain, Philippe; Tank, David W.; Burdine, Rebecca D. (Frontiers in Neural Circuits, 2014)
Larval zebrafish offer the potential for large-scale optical imaging of neural activity throughout the central nervous system; however, several barriers challenge their utility. First, ~panneuronal probe expression has to date only been demonstrated at early larval stages up to 7 days post-fertilization (dpf), precluding imaging at later time points when circuits are more mature. Second, nuclear exclusion of genetically-encoded calcium indicators (GECIs) limits the resolution of functional fluorescence signals collected during imaging. Here, we report the creation of transgenic zebrafish strains exhibiting robust, nuclearly targeted expression of GCaMP3 across the brain up to at least 14 dpf utilizing a previously described optimized Gal4-UAS system. We confirmed both nuclear targeting and functionality of the modified probe in vitro and measured its kinetics in response to action potentials. We then demonstrated in vivo functionality of nuclear-localized GCaMP3 in transgenic zebrafish strains by identifying eye position-sensitive fluorescence fluctuations in caudal hindbrain neurons during spontaneous eye movements. Our methodological approach will facilitate studies of larval zebrafish circuitry by both improving resolution of functional Ca2+ signals and by allowing brain-wide expression of improved GECIs, or potentially any probe, further into development.